Wrist-ankle acupuncture has a positive effect on cancer pain: a meta-analysis - Bei Dong; Lu Lin; Qiuyun Chen; Yishu Qi; Fen Wang; Keyan Qian; Li Tian (BMC, 2021)
Abstract Background Wrist-ankle acupuncture (WAA) as a kind of micro acupuncture therapy has been used to management cancer pain, however, the effects of WAA on cancer pain were controversial in the current studies. Therefore, the purpose of this meta-analysis was to critically evaluate the effect of wrist-ankle acupuncture (WAA) on cancer pain. Methods Seven digital databases were searched from the inception of databases to July 2020, including CNKI, Wanfang, VIP, CBM, Cochrane Library, PubMed and Embase. Randomized controlled trials conforming to the inclusion and exclusion criteria were screened and extracted; the risk of bias was evaluated using the Cochrane Collaboration criteria. The primary outcome indicators included pain relief rate and pain score, and the secondary outcome was adverse reaction incidence. All analyses were performed with Review Manager 5.3. Results A total of 13 studies with 1005 cancer patients (intervention group: 568, control group: 437) were included in this meta-analysis. The results demonstrated that the pain relief rate of experimental group (WAA / WAA + drug intervention) was better than that of control group (analgesic drug intervention), and the difference was statistically significant [RR = 1.31, 95%CI: 1.15 ~ 1.49, P < 0.01]. Conclusions WAA has certain effect on cancer pain, and the effect of WAA combined with pharmacological intervention is better than that of drug therapy alone.